A WebGIS Base Information System for Monitoring Wildfire Using Suomi-NPP (VIIRS) Satellite in Phare Province, Thailand - Jeefoo, Phaisarn (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 2 (2020): April-June 2020, 2020)
This paper is present a real-time wildfire monitoring service that exploits Suomi-NPP (VIIRS) satellite to detect hotspots and monitoring the evolution of fire fronts. The service makes heavy use of VIIRS for hotspots on national forest, forest conservation in Phare province, northern part of Thailand. GIS technology is ideally suited as a tool for the demonstration of data derived from continuous monitoring of locations and use to support and deliver information to environmental managers and public. The highest of active fire detection was 943 hotspots located in national forest (a total of 1,374 hotspots) from 15/03/2019 to 15/04/2019. Combined with GeoServer, PostgreSQL/PostGIS, it extends the WebGIS capabilities in providing real-time data from the monitoring activities. Therefore, there is a growing need of WebGIS for easy and fast distribution, sharing, displaying and processing of spatial information which in turn helps in decision making for various natural resources-based application. Keywords: Wildfire, WebGIS, GIS, Suomi-NPP (VIIRS) satellite, Active fire detection, Phare province